(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the role of choir participation in developing social skills and teamwork among students. The study aims to explore how collective music-making can foster collaboration, communication, and interpersonal relationships in a group setting. Through a combination of surveys, interviews, and observations, the research examines the impact of choir activities on students’ social development. The findings reveal that participation in choirs promotes essential teamwork skills, such as mutual respect, cooperation, and communication. Additionally, choir participation enhances students’ social confidence and helps build long-lasting peer relationships. The study concludes by recommending choir activities as an effective pedagogical tool for fostering positive social interactions in educational environments.